A panel of stomach‐specific biomarkers (GastroPanel®) for the diagnosis of atrophic gastritis: A prospective, multicenter study in a low gastric cancer incidence area. Issue 5 (23rd July 2020) - Chapelle, Nicolas; Petryszyn, Pawel; Blin, Justine; Leroy, Maxime; Le Berre‐Scoul, Catherine; Jirka, Iva; Neunlist, Michel; Moussata, Driffa; Lamarque, Dominique; Olivier, Raphael; Tougeron, David; Mosnier, Jean‐François; et al.
Abstract: Background: Analysis of serum biomarkers for the assessment of atrophic gastritis (AG), considered as gastric precancerous lesion, is of growing interest and recommended by current guidelines. Our aim was to evaluate the diagnostic performance of a panel of biomarkers (GastroPanel®) for the detection of AG in France, a country of a low gastric cancer (GC) incidence. Material and Methods: In this prospective, multicenter, cross‐sectional study, consecutive patients considered at increased risk of GC and undergoing upper endoscopy with gastric biopsies were included. Blood samples were collected for the analysis of GastroPanel® (association of Pepsinogens I and II, Gastrin‐17, and Helicobacter pylori serology) using ELISA. The results of GastroPanel® were compared to the results of histology considered as the reference. Results: Between 2016 and 2019, 344 patients (148 cases with AG, 196 controls without AG) were included. Sensitivity, specificity, positive, and negative predictive values for the detection of AG by GastroPanel® were of 39.9% (95% CI 31.9; 48.2), 93.4% (95% CI 88.9; 96.4), 81.9 (95% CI 71.1; 90.0), and 67.3 (95% CI 61.4; 72.8), respectively. The sensitivity was significantly higher for the detection of severe AG [60.8% (95% CI 46.1; 74.6) P = .015] and corpus AG [61.0% (95% CI 49.2; 72.0), P = .004]. Diagnostic performances of GastroPanel® tended to be better than those of Pepsinogen I alone, but the difference did not reach statistical significance ( P = .068). Conclusion: Serum pepsinogen and GastroPanel® tests show promising results for the detection of AG, especially of corpus AG and severe AG, in patients at high risk of GC in France.